Water Purification of Sea of Oman and Persian Gulf with Humic Acid and Measurement of Copper Ion (II) by Differential Pulse Voltammetry - Abouzar Tahkor (Journal of Global Pharma Technology, 2017)
The present research intended to remove heavy metals from the water samples of the sea of Oman and the Persian Gulf using Humic acid. The antimicrobial experiments showed that Humic acid can also remove Escherichia Coli (E. Coli) Coliform, a water pollutant, from surface water. After the removal of heavy metals ions, only copper ion (II) was measured by differential pulse voltammetry technique. Several parameters such as optimal conditions for measurement by differential pulse voltammetry, time, and pre-concentration of pH were considered in water purification and measurement of copper ion (II).The calibration curve changed linearly before passing through humic acid column 160-1 (µM), after passing through humic acid column 400-1 (µM) and after being washed with Hydrochloric acid 400-1 (µM) using standard addition technique in order to measure the concentration of copper ion in the sea of Oman. Accordingly, the concentration of copper ion (II) was obtained as 13 ppb before passing through humic acid column, 8.1 ppb after passing through humic acid column and 2.4 ppb after being washed with Hydrochloric acid column. Furthermore, the calibration curve changed linearly before passing through humic acid column 400-8 (µM), after passing through humic acid column 400-1 (µM) and after washing humic acid column with Hydrochloric acid 400-1 (µM)in order to measure the concentration of copper ion in the water of the Persian Gulf. Accordingly, the concentration of copper ion (II) was obtained as 28.72 ppb before passing through humic acid column, 14.69 ppb after passing through humic acid column, and the absorbed ion was 10.95 ppb after being washed with Hydrochloric acid column. Using standard addition technique, the limit of detection (LOD) of measured coper was calculated as1.69×10-6 (µM) in the imposed potential of the sea of Oman and -0.25×10-6 (µM) in the water of Persian Gulf.Keywords: Differential pulse voltammetry technique; Water purification of sea of Oman and Persian Gulf; Humic Acid; Copper Ion (II).